Against Structural Constraints in Subject-Verb Agreement Production - Gillespie, Maureen; Pearlmutter, Neal J (Journal of experimental psychology. Learning, memory, and cognition, 2013)
Syntactic structure has been considered an integral component of agreement computation in language production. In agreement error studies, clause-boundedness (Bock & Cutting, 1992) and hierarchical feature-passing (Franck, Vigliocco, & Nicol, 2002) predict that local nouns within clausal modifiers should produce fewer errors than do those within phrasal modifiers due to structural differences; however, Gillespie and Pearlmutter (2011b) suggested structure might play a more limited role. Two studies examined whether the clause-boundedness effect would occur when prepositional phrase modifiers and relative clause modifiers were matched in properties likely to influence the timing of planning (Gillespie & Pearlmutter, 2011b; Solomon & Pearlmutter, 2004). In both studies, more errors occurred for plural local nouns, but the clause-boundedness effect was not observed. These findings suggest that agreement computation during production does not involve a hierarchical component. (Contains 6 tables, 2 figures, and 5 footnotes.)